Sedative hypnotics use as the risk factor for fall incidents on geriatric patients - Woro Rukmi Pratiwi, Christi Mambo, Jarir At Thobari, (Universitas Gadjah Mada, 2014)
Fall incident is one of geriatric syndromes that cause an increasing public health burden worldwide.The risk factors for falls incidents on geriatric patients have been identified included medicationuse. Benzodiazepine is a sedative hypnotic that found to be associated with an increase fallincidents. The aim of the study was to evaluate the influence of sedative hypnotics on the riskof fall incidents on geriatric patients. This was an observational study using cohort designinvolving 188 eligible geriatric patients comprising 94 patients who take sedative hypnotics and94 patients who not. All pasients then underwent a test for functional mobility and fall riskusing timed âup & goâ test (TUG). The subjects who take â¤ 20 seconds to complete the TUG wasconsidered to have low risk for fall incidents, whereas those who take >20 seconds was consideredto have high risk for fall incidents. The results showed that the use of sedative hypnotics, sex,and number of drugs taken were associated with fall incidents on geriatric patients. Geriatricpatients who use sedative hypnotics were 2.41 times higher at risk of fall incidents than thosewho not use sedative hypnotics (95%CI;1.12-5.17; p=0.023). Geriatric patients who takealprazolam were 2.78 times higher at risk of fall incidents compared to those who not take(95% CI: 1.49-5.19; p=0.028). Furthermore, female geriatric patients were 3.29 times higher atrisk of fall incidents compared to male geriatic patients (95%CI: 1.58-6.88; p=0.001) and theuse of â¥ 4 kinds of drugs were 2.76 times higher at risk of fall incidents compared to the use of<4 kinds of drugs (95%CI:1.21-6.29; p=0.015). In conclusion, sedative hypnotics is found tobe a risk factor for fall incidents on geriatric patients.